Enhanced VEGF/VEGF-R and RUNX2 Expression in Human Periodontal Ligament Stem Cells Cultured on Sandblasted/Etched Titanium Disk - Marconi, Guya Diletta; Diomede, Francesca; Pizzicannella, Jacopo; Fonticoli, Luigia; Merciaro, Ilaria; Pierdomenico, Sante D.; Mazzon, Emanuela; Piattelli, Adriano; Trubiani, Oriana (Frontiers in Cell and Developmental Biology, 2020)
Bone formation, in skeletal development or in osseointegration processes, is the result of interaction between angiogenesis and osteogenesis. To establish osseointegration, cells must attach to the implant in a direct way without any deposition of soft tissue. Structural design and surface topography of dental implants enhance the cell attachment and can affect the biological response. The aim of the study was to evaluate the cytocompatibility, osteogenic and angiogenic markers involved in bone differentiation of human periodontal ligament stem cells (hPDLSCs) on different titanium disks surfaces. The hPDLSCs were cultured on pure titanium surfaces modified with two different procedures, sandblasted (Control—CTRL) and sandblasted/etched (Test—TEST) as experimental titanium surfaces. After 1 and 8 weeks of culture VEGF, VEGF-R, and RUNX2 expression was evaluated under confocal laser scanning microscopy. To confirm the obtained data, RT-PCR and WB analyses were performed in order to evaluate the best implant surface performance. TEST surfaces compared to CTRL titanium surfaces enhanced cell adhesion and increased VEGF and RUNX2 expression. Moreover, titanium TEST surfaces showed a different topographic morphology that promoted cell adhesion, proliferation, and osteogenic/angiogenic commitment. To conclude, TEST surfaces performed more efficiently than CTRL surfaces; furthermore, TEST surface results showed them to be more biocompatible, better tolerated, and appropriate for allowing hPDLSC growth and proliferation. This fact could also lead to more rapid bone–titanium integration.